2020
DOI: 10.5109/2740934
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Enhancement in the Electrical Conductivity and Reduction in the Lattice Thermal Conductivity Leading to Enhanced Thermoelectric ZT Realized by Incorporation of Metallic Nanoparticles into Oxide Matrix

Abstract: Nanoporous Fe 3 O 4 composites containing metallic Cu nanoparticles were synthesized by reducing-leaching treatment of CuFe 2 O 4 precursor. Thermoelectric properties of the composites sintered at 1270 ºC greatly improved compared with Fe 3 O 4 without Cu, presumably due to a nanoporous structure and the Cu nanoparticles remaining in the Fe 3 O 4 matrix after acid leaching. The electrical and thermal conductivity indicate that Cu in the matrix promotes the electron conduction and suppresses the phonon conducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Heat pipes have a very high thermal conductivity value, when compared to other metals heat pipes have a thermal conductivity value hundreds of times greater. With this characteristic, the heat pipe can transfer heat with a smaller decrease in temperature along the heat pipe 23,[37][38][39][40] .…”
Section: Thermoelectric Principlementioning
confidence: 99%
“…Heat pipes have a very high thermal conductivity value, when compared to other metals heat pipes have a thermal conductivity value hundreds of times greater. With this characteristic, the heat pipe can transfer heat with a smaller decrease in temperature along the heat pipe 23,[37][38][39][40] .…”
Section: Thermoelectric Principlementioning
confidence: 99%
“…All the experimental work is conducted on graphenebased composite carbon fibre using copper as tool electrode 24) , 25) . MRR and TWR were calculated from the experiments and the most influencing process parameters are observed 26) .…”
Section: Figure 4 Fabrication Process Of Metal Matrix Compositesmentioning
confidence: 99%
“…Subsequently, the friction between the two contact surfaces can be productively diminished. Moreover, the existence of nanoparticles in the base fluids might contributed to enhance a flow of mixing and provide higher thermal conductivity 17), 18) . Sharma et al 19) reported the usage of nanoparticles in nanofluid during the turning process improved the tribological properties by reducing the friction coefficient, thus reduced the machining force and tool wear.…”
Section: Introductionmentioning
confidence: 99%